STRATEGI PENERAPAN WIRELESS MESH NETWORK UNTUK PENGINGKATAN DAN KEANDALAN JARINGAN NIRKABEL - Juniarti, Tiara Sela Juniarti; Fitriah (Department of Information System Muhammadiyah University of Riau, 2025)
The need for reliable communication networks that cover a wide area is becoming increasingly important, especially in areas with limited conventional network infrastructure. One promising solution to overcome this challenge is the implementation of Wireless Mesh Network (WMN), which offers flexibility, scalability, and redundancy through direct connectivity between nodes. This study aims to design and evaluate a Wireless Mesh Network (WMN) implementation strategy to improve the reliability and performance of wireless networks. The methods used include mesh topology analysis, adaptive routing protocol selection, and network performance simulation using throughput, delay, and packet delivery ratio parameters. The preliminary results show that the implementation of Wireless Mesh Network (WMN) with proactive routing protocols such as Optimized Link State Routing (OLSR) and a hybrid approach provides an increase in throughput of up to 35% and reduces the average delay by 20% compared to traditional infrastructure-based networks. In addition, network reliability is increased through self-healing capabilities, namely the ability of the network to reset the communication path when there is a disruption to one of the nodes. These findings indicate that the right Wireless Mesh Network (WMN) implementation strategy can significantly improve the efficiency and reliability of wireless networks, especially in environments with physical or geographical limitations. This study recommends the use of adaptive mesh topology to support continuous connectivity and more resilient network management.